Dampak Pelatihan Dan Kompetensi Tenaga Pendidik Terhadap Komitmen Di Sekolah Bahasa Lembaga Pendidikan Dan Pelatihan Polri - Sukemi, Ryna Setyaningsih; Zaharuddin, Zaharuddin; Budianto, Irawan R.d (Cattleya Darmaya Fortuna, 2024)
Three important aspects influence the impact of training and competency of teaching staff on commitment at Sebasa Lemdiklat Polri, namely Seminars, Workshops and Training. The aim of the research is as follows: To determine the impact of training and competency of teaching staff on commitment in language schools at National Police Education and Training Institutions. The method used in this research is a descriptive qualitative method to create systematic, factual, and accurate information about the facts and characteristics of a particular population or area. This research was used to find out the impact of training and competency of teaching staff on the commitment of the National Police Education and Training Institute. The results of this research are the Sebasa Lemdiklat Polri's efforts to increase the competency of the certified teaching staff at the Sebasa Lemdiklat Polri, including conducting workshops, seminars, and training. The school's efforts to improve the personality competency of teaching staff as certified by the Indonesian National Police Lemdiklat National Police Education and Training Institute include guidance from the LSP (Institute for National Police Certificate) through meetings, seminars and coaching training by providing examples.